(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The interdisciplinary approach has become popular for full-service dental care. Periodontics and prosthodontics are inseparable in modern dentistry in many ways, including the treatment plan, execution of procedures, achievement of outcomes, and maintenance. Without a doubt, periodontists can provide a solid foundation for successful prosthetic outcomes by controlling inflammation and preparing sites for the appropriate prosthesis. Prosthodontists, on the other hand, could design the right restorative margin, shapes, and contacts to enhance the harmony between the prosthesis and the periodontium. This article discusses, through representative cases, potential periodontal problems and their management encountered before giving any prosthesis.